Autonomy and control in mass remote working during the Covid-19 pandemic: Evidence from a cross-professional and cross-national analysis - Marta Fana; Francesco Sabato Massimo; Angelo Moro (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
The global pandemic induced by the spread of the Covid-19 acted as an exogenous shock which forced organisations to adopt telework as a daily and common form of work along a relevant fraction of the occupational structure. Indeed, most of the growing contributions on telework focused on the estimation of employment which can work remotely, while less or any attention has been paid to the impact of the "new" work arrangement on the labour process. Our paper aims at filling this gap. Drawing from a real-time cross-professional, cross-organisational and cross-national qualitative survey, our research investigates two main and interrelated aspects. First, we show how organisations reacted to this shock in terms of autonomy and forms of control including standardisation and teamwork dimensions across different occupations and economic sectors. Second, we describe how and to which extent workers respond: adapting, resisting or appropriating the new organisation of work. More specifically, we study the effect on the above-mentioned dimensions across different occupations to highlight heterogeneity along the vertical division of labour.
Keywords: L23; M54; O33; J81; 330; Telework; Covid-19; Work organisation; Labour Process; Autonomy; Control